Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - Martínez-Alcántara, Belén; Rodriguez-Gamir, Juan; Martínez-Cuenca, Mary-Rus; Iglesias, Domingo J.; Primo-Millo, Eduardo; Forner-Giner, María A. (2017)
This work studied the hydraulic characteristics and physiological behavior of two trifoliate orange (Poncirus trifoliata L. Raft) varieties-Flying Dragon (FD) and Rubidoux (RT)-with contrasting size-controlling potential when used as rootstocks for citrus trees. Thus, Valencia orange scions growing on RT root system develop about 40 % more biomass than scions on FD. The anatomical study of xylem root tissue of both rootstocks showed that the number of vessels per cross-sectional area in RT almost doubled that found in FD, whereas diameter distribution did not vary significantly. Hydraulic resistance determined in rootstocks, and bud union segments were, respectively, 2- and 3.4-fold higher in trees on FD than in trees on RT. Root systems accounted for 46.5 and 55.2 % of whole-plant hydraulic resistance, whereas bud union segments represented 7.5 and 14.6 % of this parameter, the dwarfing rootstock (FD) having the highest values. Reduced hydraulic conductance in plants on FD rootstock diminished water potential in high evaporative demand periods, causing a reduction in stomatal conductance with respect to plants on RT. This leads to lower net photosynthetic CO2 assimilation, which may affect biomass production. Translocation of C-13-labeled photoassimilates from leaves to roots was lower in plants on FD than in plants on RT, indicating that in the dwarfing rootstock (FD) there may be a vascular resistance to sucrose transport at the budding union level. Findings show that reduced hydraulic conductance may be the main cause of rootstock-induced dwarfing in citrus grafted onto FD.